Analysis of the results of prostate cancer biopsies performed after a 10-year interval - I. Romics (Onkourologiâ, 2008)
Introduction and objective: the authors compared the results of biopsies performed in 1994 and 2004, respectively.The analysis of the results of prostate biopsy obtained in 1994 and 2004 was carried out. Prostate cancer is the most common malignant tumor in males; its diagnostic algorithm and therapy were analyzed. The aim of the study was to compare data from the prostate biopsies performed in 1994 with those of 2004. During this decade, 4.5 fold increase of the number of prostate biopsies has been observed. In 1994, 36.2%, while in 2004, 47.5% of the biopsies proved to be a cancer. The mean age of the patients undergoing biopsy decreased from 69.7 to 62.3 years; however, the mean age of patients who were suffering from prostate cancer remained constant (70.8 vs. 71.3 years).Conclusions: Whereas in 1994 only the total level of PSA was estimated, in 2004 the diagnostic algorithm included additional measurements of free-PSA and PSA-density. Prostate biopsy was performed by a trans-rectal ultrasound guided technique unlike the blind or trans-perineal methods which were only available previously. Although the effectiveness of the prostate biopsy is improved, the diagnosis and identification of prostate cancer at a younger age remains to be a challenge. The Gleason score marking the aggressiveness of the prostate cancers was lower; therefore, more patients were found suitable for curative surgery. However, the increased mean value of PSA level indicated that patients were still rather of a more advanced stage in majority, which could only be treated by palliative therapy.